PREVALENCE OF GASTROINTESTINAL TRACT DISEASES AND EFFICACY OF ERADICATION THERAPY FOR H.PYLORI INFECTION IN CHILDREN - I.A. Zhdanova; L.S. Namazova; A.G. Ilyin (Вопросы современной педиатрии, 2006)
Prevalence of upper gastrointestinal tract pathology and estimations of clinical and pharmacoeconomic efficacy of different algorithms of therapy for H. pyloria assosiated diseases in children dwelling in Krasnodar region are presented in this article. Key words: h. Pylori, prevalence, treatment, eradication therapy, children.